Students Creative Thinking Skills in the Context of Handling Fish Bone Waste with Problem-Based Learning Model - Mufida, Irmitha; Rosbiono, Momo; Sopandi, Wahyu (Journal of Educational Sciences, 2021)
This study aims to build students' creative thinking skills in the context of handling fish bone waste by using a Problem-Based Learning model. The research method applied was Developmental Research with pre-experimental research design one group pretest-posttest. This research was conducted at one of the MANs located in Medan City. The sample in this study were 32 students of class XI IPA in the even semester of the 2019/2020 school year. Research activities were carried out online with the help of the WhatsApp application and zoom. The research instrument used the form of 12 essay items on the validated student worksheets (LKS) and suitable for measuring students' creative thinking skills. The data obtained from this study were analyzed quantitatively using Microsoft Excel and SPSS software. The results showed that students' creative thinking skills in the context of handling fish bone waste by using a problem-based learning model were included in the "Good" category with an average overall percentage of 63%.